(untitled) (Jurnal Riset Mahasiswa, 2023)
In order to support good public service delivery, a performance management system is needed to guide employees in carrying out their duties and functions. Every job must be well planned, well executed, and its performance can be accounted for. For this reason, a performance appraisal system is needed that can measure individual and organizational performance achievements. The measurement aspects include workload and performance achievements. This study aims to identify the factors causing the low workload measurement results and strategies to improve performance in the Regional Financial Board of Pacitan Regency. After conducting the research, it was concluded that the factors causing the low measurement of employee workload at the Regional Finance Board were (1) low motivation or work ethic, (2) poor example from more senior colleagues, (3) management bad timing, (4) less strict enforcement of rules, and (5) notification of a violation. While the strategies that can be implemented to overcome the above problems are (1) Developing an action plan for evaluating previous year performance achievements, (2) Providing rewards and punishments for performance achievements, (3) Expanding the use of IT or applications to speed up and simplify work, ( 4) Increasing employee discipline through dissemination of employment rules, (5) Increasing employee capacity through training and technical guidance, (6) Conducting periodic performance evaluations, (7) Fulfillment of work facilities and infrastructure, and (8) Increasing employee welfare. Guna mendukung penyelenggaraan pelayanan publik yang baik diperlukan sistem manajemen kinerja yang menjadi pedoman bagi pegawai dalam melaksanakan tugas dan fungsinya. Setiap pekerjaan harus direncanakan dengan baik, dilaksanakan dengan baik, dan kinerjanya dapat dipertanggungjawabkan. Untuk itu diperlukan sistem penilaian kinerja yang dapat mengukur capaian kinerja individu dan organisasi. Aspek pengukurannya meliputi beban kerja dan capaian kinerja. Penelitian ini bertujuan untuk mengidentifikasi faktor penyebab masih rendahnya hasil pengukuran beban kerja serta bagaimana strategi untuk meningkatkan kinerja di Badan Keuangan Daerah Kabupaten Pacitan. Setelah dilakukan penelitian, ditarik kesimpulan bahwa faktor-faktor yang menyebabkan rendahnya pengukuran beban kerja pegawai di Badan Keuangan Daerah adalah (1) Motivasi atau etos kerja yang rendah, (2) Keteladanan yang kurang baik dari reka kerja yang lebih senior, (3) Manajemen waktu yang kurang baik, (4) Penegakan aturan yang kurang tegas, dan (5) Adanya pemakluman terhadap suatu pelanggaran. Sedangkan strategi yang dapat dilakukan untuk mengatasi masalah di atas adalah (1) Menyusun rencana aksi atas evaluasi capaian kinerja tahun sebelumnya, (2) Memberikan reward dan punishment terhadap pencapaian kinerja, (3) Memperluas penggunaan TI atau aplikasi untuk mempercepat dan mempermudah perkerjaan, (4) Meningkatkan kediplinan pegawai melalui sosialisasi aturan kepegawaian, (5) Meningkatkan kapasitas pegawai melalui diklat dan bimbingan teknis, (6) Melalukan evaluasi kinerja secara berkala, (7) Pemenuhan sarana dan prasarana kerja, dan (8) Peningkatan kesejahteraan pegawai.